2000
DOI: 10.1016/s0304-3959(99)00192-x
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted infrared thermographic study of axon reflex induced by intradermal melittin

Abstract: The aim of the present study was to investigate whether melittin, the principal toxin of the honeybee (Apis mellifera) venom, can be used as an algogenic agent in the study of pain in humans. Five micrograms of melittin in 0.5 ml of saline was intradermally injected into the volar aspect of the forearm. Resultant pain was scored by a visual analogue scale (VAS), and skin temperature change was analyzed by means of a computer-assisted infrared thermography. Intradermal melittin temporarily produced severe pain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
1
19
0
2
Order By: Relevance
“…This result was not likely due to systemic effects of the two drugs since local injection of the two antagonists in the non-injected paw did not have any significantly pharmacological influence upon melittin-induced nociception and hypersensitivity. Human experiments showed that intradermal injection of melittin could elicit severe spontaneous pain, followed by sustained increase in skin temperature and a process of neurogenic inflammation (visual flare) accompanied by heat or mechanical hyperalgesia [20][21][22][23]. Similar results have also been obtained from our research in rats [11,12].…”
Section: Discussionsupporting
confidence: 88%
“…This result was not likely due to systemic effects of the two drugs since local injection of the two antagonists in the non-injected paw did not have any significantly pharmacological influence upon melittin-induced nociception and hypersensitivity. Human experiments showed that intradermal injection of melittin could elicit severe spontaneous pain, followed by sustained increase in skin temperature and a process of neurogenic inflammation (visual flare) accompanied by heat or mechanical hyperalgesia [20][21][22][23]. Similar results have also been obtained from our research in rats [11,12].…”
Section: Discussionsupporting
confidence: 88%
“…To date, the mean areas (mm 2 ) of temperature above basal peak temperature, e.g. in ranges of 0.2°C, have usually been calculated (Koyama et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to increased interest in animal studies on bee venom-induced nociception or pain, the first experimental study on pain and inflammatory responses of seven healthy adults (2 women and 5 men) to intradermal (i.d.) injection of melittin was carefully conducted and published in 2000 (Koyama et al, 2000). The human subjects reported the pain intensity experienced using a 0–10 visual analog scale (VAS) in which scores of 0, 5 and 10 indicated “no pain”, “moderate pain” and “intolerable pain”, respectively.…”
Section: Nociceptive and Inflammatory Effects Of Subcutaneous Bee mentioning
confidence: 99%